2022
DOI: 10.3390/ijms23084086
|View full text |Cite
|
Sign up to set email alerts
|

Asthmatic Eosinophils Alter the Gene Expression of Extracellular Matrix Proteins in Airway Smooth Muscle Cells and Pulmonary Fibroblasts

Abstract: The impaired production of extracellular matrix (ECM) proteins by airway smooth muscle cells (ASMC) and pulmonary fibroblasts (PF) is a part of airway remodeling in asthma. This process might be influenced by eosinophils that migrate to the airway and abundantly secrete various cytokines, including TGF-β. We aimed to investigate the effect of asthmatic eosinophils on the gene expression of ECM proteins in ASMC and PF. A total of 34 study subjects were recruited: 14 with allergic asthma (AA), 9 with severe non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
0
8
0
1
Order By: Relevance
“…Notably, mast cell activation syndrome (MCAS) is highly prevalent in ME/CFS and connective tissue disorders, including EDS/hEDS/HSD. Additionally, aberrant eosinophil function is commonly observed in connective tissue disorders ( 167 , 168 ) and reported in the context of ME/CFS ( 169 , 170 ). This underscores the necessity for further exploration into the dynamic interactions between mast cell and eosinophil immune responses and connective tissue function in ME/CFS ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, mast cell activation syndrome (MCAS) is highly prevalent in ME/CFS and connective tissue disorders, including EDS/hEDS/HSD. Additionally, aberrant eosinophil function is commonly observed in connective tissue disorders ( 167 , 168 ) and reported in the context of ME/CFS ( 169 , 170 ). This underscores the necessity for further exploration into the dynamic interactions between mast cell and eosinophil immune responses and connective tissue function in ME/CFS ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 It was found that MMP2 possessed the capability to enhance the infiltration and aggregation of eosinophils at the inflammation site through its control over the degradation of the extracellular matrix and the dissociation of extracellular matrix molecules. 49 Moreover, a prior study revealed that the increased expression of MMP-2 and MMP13 in allergic nasal mucosa could expedite eosinophil migration to the nasal mucosa among patients with allergic rhinitis. This observation underscored the dynamic participation of MMPs in the pathogenesis of allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…The ECM (also matrisome) is a complex non-cellular three-dimensional macromolecular network present within all tissues and organs, forming the foundation on which cells sit. It is composed of 1. structural and specialized proteins (such as collagens, elastin, fibrillin, laminin, fibronectin, vitronectin, nidogen also known as entactin, tenascin, amelogenins, dentin sialoprotein, and dentin phosphoprotein), 2. glycosaminoglycans, also known as mucopolysaccharides (hyaluronan, heparin, heparan sulphate, chondroitin sulphate, keratan sulphate, and dermatan sulphate), which are the major components of proteoglycans (proteins that contain covalently linked glycosaminoglycans, such as syndecan, betaglycan, perlecan, aggrecan, decorin, andversican), 3. minerals (hydroxyapatite and derivatives found in bone or dentine), 4. lipids, 5. water, and 6. tissue-bound growth factors [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The most abundant proteins of the ECM are collagens [ 17 , 18 ].…”
Section: The Extracellular Matrixmentioning
confidence: 99%